Isu Kontemporer Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah: Contemporary Issues in Arabic Language Learning in Elementary Islamic Schools - Kamila, Farichatul; Aisa, Firda; Susilawati, Sinta Ayu; Abu Bakar, M. Yunus (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
The purpose of Arabic language learning in elementary Islamic schools has not yet achieved the intended goals, which include the four language skills: speaking, reading, listening, and writing. Based on the results of a field survey at Wahid Hasyim Elementary Islamic School in Yogyakarta, the purpose of Arabic language learning only prioritizes two skills, namely speaking and listening, where students are required to communicate using Arabic. However, the other two skills are addressed. According to the author, the Arabic language material in elementary Islamic schools is not ideal because many materials are taught in a sequence of straightforward, complex, moderate, challenging, and accessible, complicating students' receiving the prepared material. In contrast, the material should ideally start from easy, medium, and then hard to facilitate students' learning. In Arabic language learning in elementary Islamic schools, the "nadzariyatul wahdah" (all-in-one system) approach is ideal, where Arabic is taught from various skill aspects without separating the language. Pada dasarnya tujuan pembelajaran bahasa arab di madrasah ibtidaiyah belum mencapai tujuan yang diharapkan meliputi 4 kemahiran berbahasa yaitu kalam, qira’ah, istima’, dan kitabah. Berdasarkan hasil survey lapangan di Madrasah Ibtidaiyah Wahid Hasyim Yogyakarta tujuan bahasa arab hanya memprioritaskan 2 kemahiran saja yaitu kalam dan istima dimana siswa dituntut untuk dapat berkomunikasi menggunakan bahasa arab, meskipun 2 kemahiran lainnya tidak diabaikan.Materi bahasa arab di Madrasah Ibtidaiyah menurut penulis belum ideal karena banyak materi yang diajarkan berawal dari mudah- sukar- sedang- sukar- mudah yang menyulikan peserta didik dalam menerima materi yang diajarkan, sedangkan idealnya materi itu berawal dari mudah- sedang- lalu sukar agar memudahkan peserta didik dalam menerima pelajaran.Pada pembelajaran bahasa arab di Madrasah Ibtidaiyah idealnya menggunakan nadzariyatul wahdah (all in one system) yang mana bahasa arab diajarkan dari berbagai aspek kemahiran tanpa memisah- misahkan bahasa tersebut.